Perancangan Fasilitas Kerja pada Operator Menggunakan Metode SNQ dan REBA dengan Software Ergofellow - Fitriadi, Fitriadi; Putra, Gaustama; Avina, Avina (Jurnal Optimalisasi, 2021)
Agam Teknik is a business that produces dump trucks, where at the iron plate cutting site there are no work facilities that support operators in carrying out their work activities which result in complaints of skeletal muscles. In the production process activities, it was found that there were semi-automatic activities, namely the process of cutting iron plates using a welding torch on the floor so that the operator worked in a squatting state, bent knees and ankles, raised shoulders and bent body so that the work posture experienced by the operator was not ergonomic. The aims of this study were (1) to identify complaints of musculoskeletal disorders experienced by dump truck manufacturing operators using the Standard Nordic Quistionaire (SNQ), (2) to determine the value of the operator's work posture using the REBA method with the help of Ergofellow Software, and (3) to design ergonomic work facilities. SNQ is a method used to identify the source of muscle fatigue at work, while the REBA method is used to determine risk factors related to overall body posture at work. The tool used is Ergofellow Software which serves to analyze quickly and easily in terms of postural. The results of the identification of operator complaints during the dump truck manufacturing process, obtained two work stations where the operator felt very sick and painful complaints, namely at the cutting station and pressing the iron plate. Based on the identification results obtained eight operator complaints, namely extreme pain and pain including pain in the left and right shoulders, neck pain, left upper arm pain, back pain, left hand pain, right knee pain, left calf pain, and pain in the right leg. Recommendations from these conditions are to design an iron plate cutting work facility with the addition of a table for cutting iron plates, and to redesign the iron plate pressing station by adjusting the press tool used by the operator for pressing iron plates.